Rehabilitation of the south american genus ochetophila poepp. ex endl. (Rhamnaceae: Colletieae) - Kellermann, J. (2005)
Recent molecular and morphological analyses show that Discaria is polyphyletic and consists of two separate clades, Discaria sens. str. and a clade of two species from Chile and Argentina: D. trinervis and D. nana. The genus Ochetophila is here reinstated to accommodate these two species. A revised synonymy is presented, and a new combination is provided for O. nana.